Essays on maternal employment and child health outcomes - Wasswa, Gabriel (2019)
This thesis is composed of five chapters including three essays of original work relating to maternal employment and child health outcomes. The first chapter provides a motivation, a brief description of the data used and a summary of the findings. Chapter two, forms one of the three essays and provides findings on the impact of maternal employment and household socio-economic status on child health. The chapter uses data from Uganda Demographic and Health Surveys (UDHS) for 2006 and 2011. Chapter three is the second essay in this thesis and again uses Uganda Demographic and Health Surveys for the same years 2006 and 2011 but with a different unit of analysis from the second chapter, as it focuses on mothers instead of children. It investigates factors that influence mothers’ decision choices for employment and subsequently the employment sector. The last essay forms chapter four which uses a UK rich data set of ‘Understanding Society’ to investigate the impact of maternal employment on a child’s happiness. We make our general conclusion in chapter five and the appropriate recommendations.